Zymographic patterns of MMP-2 and MMP-9 in the CSF and cerebellum of dogs with subacute distemper leukoencephalitis - Machado, Gisele Fabrino [UNESP]; Melo, Guilherme D. [UNESP]; Souza, Milena S. [UNESP]; Machado, Andressa A. [UNESP]; Migliolo, Daniela S. [UNESP]; Moraes, Olívia C. [UNESP]; Nunes, Caris Maroni [UNESP]; Ribeiro, Érica S. [UNESP] (Elsevier, 2013)
Distemper leukoencephalitis is a disease caused by the canine distemper virus (CDV) infection. It is a demyelinating disease affecting mainly the white matter of the cerebellum and areas adjacent to the fourth ventricle; the enzymes of the matrix metalloproteinases (MMPs) group, especially MMP-2 and MMP-9 have a key role in the myelin basic protein fragmentation and in demyelination, as well as in leukocyte traffic into the nervous milieu. To evaluate the involvement of MMPs during subacute distemper leukoencephalitis, we measured the levels of MMP-2 and MMP-9 by zymography in the cerebrospinal fluid (CSF) and in the cerebellum of 14 dogs naturally infected with CDV and 10 uninfected dogs. The infected dogs presented high levels of pro-MMP-2 in the CSF and elevated levels of pro-MMP-2 and pro-MMP-9 in the cerebellar tissue. Active MMP-2 was detected in the CSF of some infected dogs. As active MMP-2 and MMP-9 are required for cellular migration across the blood-brain barrier and any interference between MMPs and their inhibitors may result in an amplification of demyelination, this study gives additional support to the involvement of MMPs during subacute distemper leukoencephalitis and suggests that MMP-2 and MMP-9 may take part in the brain inflammatory changes of this disease. © 2013 Elsevier B.V.
Keywords: Canine distemper virus; Central nervous system; Inflammation; Matrix metalloproteinases; Zymography; gelatinase A; gelatinase B; animal tissue; blood brain barrier; canine distemper; Canine distemper morbillivirus; cell migration; cerebellar peduncle; cerebrospinal fluid; controlled study; dog; enzyme activity; ependyma cell; microglia; molecular weight; mononuclear cell; nonhuman; retina rod; zymography; Canis familiaris